Economic Transformation and the Return to Human Capital - The Case of Hungary, 1986-1996 - Maria Vincze; Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1999)
Millions of East-Europeans started businesses during the transformational recession but, according to a wide-spread interpretation, many of them did so only temporarily and 'unwillingly' under the threat of unemployment. The paper looks at the relevance of the 'disguised unemployment approach to entrepreneurship' using regional data.It first examines how net flows into self-employment were affected by corporate labour demand in Hungarian and Romanian regions. Second, it looks at the responses of self-employment and unemployment to increases in labour demand at later stages of the transition. Finally,.it makes attempts to measure the 'wage push' of selfemployment. The evidence suggests that self-employment and unemployment were guided by rather different forces In Hungary. By contrast, the Romanian agriculture absorbed a non-trivial proportion of the potential unemployed following the unique land reform and the introduction of a restrictive UI system. The data suggest larger flows into self-employment in regions hit hard by the transition shock but they do not indicate net flows from self-employment back to paid employment in the few Romanian regions where labour demand was rising between 1993 and 1996. The pool of private farmers failed to behave as a 'reserve army' in this period and did not have strong influence on wage claims at the enterprise sector.
Keywords: 330